Physicochemical post-harvest changes that affect the quality of palm clusters Elaeis oleifera (Kunth) cortés x Elaeis - Montoya P., Luz Karime; Osorio M., Oswaldo; Cerón C., Andrés Felipe (Revista de Ciencias Agrícolas, 2014)
High Oleic material differs in various aspects from the variety E. guineensis Jacq. (the only commercially managed variety in the region of Tumaco, Nariño, Colombia), therefore, it is necessary to evaluate post-harvest variables that influence the quality and productivity of clusters, such as: moisture loss, fruit breakdown or unshelling, and increase in free fatty acids (FFA), as factors that are potentiated during storage. This study monitored the three variables mentioned above in two environments, under shade and exposed, in order to determine the resulting effects. It was determined that 90% of the clusters lost at least 101,33 g ± 15,01 of their initial weight, equal to 1,01% ± 0,0015 of the cluster’s total weight harvested. After 30 days, the cluster lost 25,02% ± 2,34 of its total weight. With respect to unshelled fruit, it was determined that after five days, 100% of the fruits were loose in both of the evaluated environments. The FFA content under shade and exposed was 2,56% ± 2,62 and 0,22 ± 0,26%, respectively, atday 11; past this time, FFA content percentages exceed the maximum allowed. In conclusion, the maximum storage time under shade and exposed is 11 days.